A Comparison of Guided Bone Regeneration vs. the Shell Technique Using Xenogeneic Bone Blocks in Horizontal Bone Defects: A Randomized Clinical Trial - Paolo De Angelis; Camilla Cavalcanti; Paolo Francesco Manicone; Margherita Giorgia Liguori; Edoardo Rella; Giuseppe De Rosa; Alberto Palmieri; Antonio D'Addona (MDPI AG, 2024)
In cases of severe horizontal atrophy, implant placement requires bone reconstruction procedures. The aim of this randomized controlled trial is to compare the outcomes of bone augmentation with simultaneous implant placement using the shell technique to the outcomes of guided bone regeneration (GBR) in cases of severely horizontal bone atrophy. This study was designed as a monocentric, parallel-group, randomized controlled trial with a six-month follow-up. Among the primary outcomes of this study, peri-implant bone regeneration and peri-implant bone defect closure were selected. Forty-four patients were recruited and equally divided between two groups. In the GRB group, a horizontal regeneration of 2.31 ± 0.23 mm was observed opposed to a horizontal regeneration of 2.36 ± 0.17 mm in the shell group (p = 0.87). A volumetric increase was observed in both groups, with an increase of 0.30 ± 0.12 cm3 in the GBR group and an increase of 0.39 ± 0.09 cm3 in the shell group, highlighting a significant difference between the two groups (p = 0.02). In conclusion, bone augmentation with simultaneous implant placement using the shell technique or guided bone regeneration in horizontal bone atrophy are both predictable therapeutic options.